Health and Safety in Canadian Workplaces - Foster, Jason; Barnetson, Bob (Open paths to enriched learning, 2016)
Workplace injuries happen every day and can profoundly affect workers, their families, and the communities in which they live. This textbook provides workers and students with an introduction to effective injury prevention. It pays particular attention to how issues of precarious employment, gender, and ill-health can be better handled in Canadian occupational health and safety (OHS). Health and Safety in Canadian Workplaces offers an extensive overview of central OHS concepts and practices and provides practical suggestions for health and safety advocacy. It attempts to bring OHS into a twenty-first century context by discussing contemporary workplaces and the health effects of new work processes and structures while recognizing that safety has gendered and racialized dimensions. Foster and Barnetson contend that the practice of occupational health and safety can only be understood if we acknowledge that workers and employers have conflicting interests. Who identifies what workplace hazards should be controlled is therefore a product of the broader political economy of employment and one that should be well understood by those working in the field. -- Publisher's description. Contents: Workplace injury in theory and practice -- Legislative framework of injury prevention and compensation -- Hazard recognition, assessment and control -- Physical hazards -- Chemical and biological hazards -- Psycho-social hazards -- Health effects of employment -- Training and injury prevention programs -- Incident investigation -- Disability management and return to work -- The practice of health and safety.
Keywords: Canada; Industrial safety